Linking practices to results: an analysis toward Lean Six Sigma deployment in the public sector - Juliani, Fernando [UNESP]; de Oliveira, Otávio José [UNESP] (Emerald, 2020)
Purpose: The purpose of this paper is to present relationship between operation and management practices analyzing the results achieved by both public organizations prone to deploy Lean Six Sigma (LSS) and public organizations that have already implemented the method. The goal is to support the start of method deployment by public managers and the creation of more efficient and effective processes in public organizations. Design/methodology/approach: An analysis of synergies between findings in the multiple case study carried out in Brazilian public organizations from health and education sectors and successful implementations found in the LSS literature is made. Findings: The fact that this research comprised organizations from different segments allowed good practices and difficulties to be identified in a unique way, adding more value to the research carried out and increasing the potential of support to the public manager. In addition, it was possible to map the most mentioned benefits of LSS deployment in both health and education sectors and link them to systematized LSS practices. Research limitations/implications: The presenting research should initiate a scientific discussion on public sector areas more prone to LSS and guide researchers in the development of case studies aimed at the application of this method in public organizations in general. Practical implications: This paper can assist public managers to become aware of the potential of the organization they manage in the adoption of LSS principles and practices enabling a better quality of services provided to citizens. Originality/value: The finding that public health organizations are more likely to implement LSS principles and practices when compared to public organizations from other segments can guide more in-depth studies that justify why some organizations would be better able to implement the LSS method and others would face more difficulties in a hypothetical deployment.
Keywords: Lean six sigma; Multiple case study; Performance; Public organization